ANALISIS RASIONALITAS OBAT DIABETES MELITUS TIPE II DI UPT PUSKESMAS SAKETI PERIODE JULI-DESEMBER 2023 - Santi, Santi Endrawati; Maimunah, Sariyati; Cahyadi, Andi (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by chronic hyperglycemia, the treatment process must be carried out rationally, including correct diagnosis, correct patient, correct drug, correct dose, correct indication and correct time interval. This study aims to determine the rationality of the use of antidiabetic drugs at the Saketi Health Center UPT in the period July-December 2023. Retrospective data collection based on medical records using the Total sampling method was carried out on 138 samples that had met the inclusion and exclusion criteria. Data analysis using univariate analysis using the Microsoft Office Excel 2010 program, data was analyzed using the 2021 Perkeni literature and the Indonesian Ministry of Health 2019 for the rationality of 138 Diabetes Mellitus (DM) patients. Patient characteristics in the form of gender, there is a percentage of women 99 (72%) and men 39 (28%), Diabetes Mellitus (DM) which often occurs in the age range of 46-65 years with 110 cases (80%) The percentage of rationality of the use of diabetes mellitus drugs in patients with the right diagnosis is 138 patients 100%, right patients 138 100%, right drug selection 26 (19%) patients, wrong drug selection 112 (81%), right indication 138 patients 100%, right dose patients 138 100% and interval time of administration 138 patients.